T43. PREDNISOLONE VERSUS PLACEBO AS AUGMENTATION THERAPY IN PSYCHOTIC DISORDERS. (18th May 2020) - Lyliana, Nasib; Winter, Inge; Kahn, Rene; Sommer, Iris
Abstract: Background: An increasing body of evidence suggests that immune dysregulation is involved in the pathophysiology of psychotic disorders. Some, but not all, anti-inflammatory drugs have shown positive effects on symptom severity. Given the need for new treatment options in psychosis, anti-inflammatory medication should be explored as a potential treatment to improve outcome. Being a potent glucocorticosteroid that adequately passes through the blood-brain barrier, prednisolone qualifies as a potential candidate. This proof-of-concept study aims to explore the effect of prednisolone, compared to placebo, on symptom severity in patients with a psychotic disorder who are on a stable dose of antipsychotic medication. Methods: The study was conducted from July 2015 until April 2019 in four centers in the Netherlands and Belgium. Patients with a psychotic disorder were randomized, double blind, 1:1 to prednisolone or placebo in addition to their antipsychotic treatment. Patients randomized to prednisolone started with 40 mg/day, tapered down to zero in six weeks. Several procedures were implemented to ensure patient safety during prednisolone exposure (e.g. regular safety labs). The primary objective was to compare change in symptom severity, measured through the Positive and Negative Syndrome Scale (PANSS), in patients treated with prednisolone versus placebo, in additional to a stable antipsychotic regimen. To this end, a mixed model repeated measures ANOVA was applied. Results: 42 participants were randomized, equally divided across the treatment arms. The six week treatment period was completed by 20 patients randomized to placebo and 19 patients randomized to prednisolone. There were no baseline differences in demographics, symptom severity, depression or global functioning between the treatment groups. There was no difference in symptom improvement between patients treated with prednisolone compared to placebo at the end of the six week treatment period (p=.304). Global functioning and depression were not significantly different between treatment arms end of treatment. No Serious Adverse Events (SAEs) occurred during the treatment phase. Discussion: The results of this proof-of-concept study do not support the immune hypothesis of psychosis: there was no difference in symptom improvement after a six week treatment with prednisolone compared to placebo, in addition to a stable regimen of antipsychotics. The small sample size is the main limitation of this trial. Even though prednisolone did not show to be a potential candidate for augmentation therapy in psychosis, it is of interest to note that patients did not deteriorate when using prednisolone nor were there more SAE's in the active treatment arm. This argues against the general safety concerns for prescribing prednisolone in patients with psychosis for the treatment of immune disorder, although additional research is needed.